2012
DOI: 10.5772/51088
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Various Forecasting Methods for Autocorrelated Time Series

Abstract: The accuracy of forecasts significantly affects the overall performance of a whole supply chain system. Sometimes, the nature of consumer products might cause difficulties in forecasting for the future demands because of its complicated structure. In this study, two machine learning methods, artificial neural network (ANN) and support vector machine (SVM), and a traditional approach, the autoregressive integrated moving average (ARIMA) model, were utilized to predict the demand for consumer products. The train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The approach consisted of a combination of discrete wavelet theory, ANNs and an adaptive-network-based fuzzy inference system. Further studies offered a comparison of ANN with more traditional tools for demand forecasting; to be more precise, Kandananond (2012) and Shahrabi et al (2009) compared ANNs with ARIMA models, moving average, exponential smoothing and exponential smoothing with trend. Benkachcha et al (2014) and Lu et al (2012) have shown that ANN models provide more accurate forecasting compared to multiple linear regression and other AI tools.…”
Section: Imds 1194mentioning
confidence: 99%
“…The approach consisted of a combination of discrete wavelet theory, ANNs and an adaptive-network-based fuzzy inference system. Further studies offered a comparison of ANN with more traditional tools for demand forecasting; to be more precise, Kandananond (2012) and Shahrabi et al (2009) compared ANNs with ARIMA models, moving average, exponential smoothing and exponential smoothing with trend. Benkachcha et al (2014) and Lu et al (2012) have shown that ANN models provide more accurate forecasting compared to multiple linear regression and other AI tools.…”
Section: Imds 1194mentioning
confidence: 99%
“…A survey of predicting stock market returns showed that non-linear models are better for forecasting the returns in emerging and frontier markets [9]. For predicting the market demand [10] and also improving the academic performance of the institution [11], the ANN model gives better accuracy as compared with other advanced models [12]. In a study on predicting the electricity demand in Thailand, the ANN model showed a more significant prediction [13].…”
Section: Introductionmentioning
confidence: 99%
“…The two methods are used to forecast the failure of the system. 8 Aburto and Weber 9 combined the two forecasting methods which are ARIMA and neural networks. The efficiency of the hybrid model is compared with traditional forecasting methods.…”
Section: Introductionmentioning
confidence: 99%